The role of the MicroBiome in PANCreatic cancer and its precursors— the study protocol of the MiBiPanc systematic review and meta-analysis - My-Lan Pianka; Alexander Werba; Samuel Zimmermann; Johannes A. Vey; Eva Kalkum; Solveig Tenckoff; Andrew Tony-Odigie; Christoph W. Michalski; Frank Pianka (Systematic Reviews)
Abstract Background Pancreatic cancer is the third leading cause of cancer-related death in Northern America and fourth in Europe. Emerging evidence suggests that the pancreatic microbiome may play a significant role in the development and progression of this disease. Although the human microbiota contributes to health by supporting nutritional and hormonal homeostasis, modulating inflammation, detoxifying harmful compounds, and producing beneficial metabolites, several studies have implicated its crucial modulatory role in numerous diseases, including cancer. The main objective of this review is to investigate the specific relationship between the microbiome and pancreatic carcinogenesis. Methods A comprehensive literature search will identify studies examining the microbiome in human samples of saliva, pancreatic fluid, bile, pancreatic tissue, and feces of patients with chronic pancreatitis, precancerous pancreatic lesions, and pancreatic cancer. Studies differentiating bacteria to at least the genus level will be prioritized. Eligible studies include randomized controlled trials and observational studies analyzing the human microbiome in patients with chronic pancreatitis, pancreatic precursor lesions, or pancreatic cancer compared to healthy controls. Studies analyzing nonhuman samples, single bacterial strains, or lacking comparator groups will be excluded. The following databases will be searched without any restrictions to the publication date up until December 2024: the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE (via PubMed), Embase, and Web of Science. Animal studies, case reports, and studies not reporting analyses of human samples are excluded. Details regarding blinding, risk of bias, and funding sources will be extracted and assessed. The main outcomes include the bacterial diversity in each sample type (stool, saliva, bile, intratumoral, and tissue) itemized for each diagnosis, identifying differentially abundant or depleted taxa, and evaluating the correlation of specific bacteria with disease prevention or progression and clinical outcomes. Data extraction will be performed independently by two reviewers. Risk-of-bias assessment will be performed using Cochrane tools appropriate for each study design. Comparisons will be analyzed by descriptive statistics, and meta-analyses will be performed when applicable. The review will be conducted according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. Discussion In summary, this systematic review aims to synthesize studies analyzing microbiome profiles in patients with chronic pancreatitis, precursor lesions, and pancreatic cancer, focusing on identifying bacterial diversity and specific taxa related to disease progression and development of cancer in comparison to healthy controls and will include a thorough critical appraisal of the available literature. Anticipated limitations include heterogeneity in microbiome sampling methods and potential variability in taxonomic resolution across studies. Systematic review registration PROSPERO CRD42023487995.